Systemic Vasculitis Imaging Features - Hendaoui, Lotfi; Stanson, Anthony W.; Bouhaouala, M. Habib; Joffre, Francis (Diagnostic Imaging,, 2012)
Vasculitis is a clinicopathologic process characterized by inflammation of and damage to blood vessels. Vessels of any type and size in any organ can be affected, resulting in a wide range of signs and symptoms. While patients with systemic vasculitis are relatively uncommon in vascular practice, a missed diagnosis can be disastrous. It is therefore imperative to achieve the correct diagnosis promptly and to initiate treatment as quickly as possible. Imaging is of vital importance in the diagnosis of systemic vasculitis, and in some cases it also plays a role in endovascular treatment. In this book, the imaging features of the many different types of vasculitis are clearly demonstrated by means of numerous high-quality illustrations. All relevant imaging modalities are considered, and key distinctive characteristics are highlighted. In addition, each chapter discusses the etiology, epidemiology, pathogenesis, clinical presentation, biology, and treatment of the vasculitis in question. This book is the result of cooperation between expert teams from a range of countries. The wealth of illustrations and informative clinical case studies will prove invaluable for all who may be confronted with these problematic disorders.